Detailed characterizations of cranial nerve anatomy in E14.5 mouse embryos/fetuses and their use as reference for diagnosing subtle, but potentially lethal malformations in mutants - Reissig, Lukas F.; Geyer, Stefan H.; Winkler, Viola; Preineder, Ester; Prin, Fabrice; Wilson, Robert; Galli, Antonella; Tudor, Catherine; White, Jaqueline K.; Mohun, Timothy J.; Weninger, Wolfgang J. (Frontiers in Cell and Developmental Biology, 2022)
Careful phenotype analysis of genetically altered mouse embryos/fetuses is vital for deciphering the function of pre- and perinatally lethal genes. Usually this involves comparing the anatomy of mutants with that of wild types of identical developmental stages. Detailed three dimensional information on regular cranial nerve (CN) anatomy of prenatal mice is very scarce. We therefore set out to provide such information to be used as reference data and selected mutants to demonstrate its potential for diagnosing CN abnormalities. Digital volume data of 152 wild type mice, harvested on embryonic day (E)14.5 and of 18 mutants of the Col4a2, Arid1b, Rpgrip1l and Cc2d2a null lines were examined. The volume data had been created with high-resolution episcopic microscopy (HREM) as part of the deciphering the mechanisms of developmental disorders (DMDD) program. Employing volume and surface models, oblique slicing and digital measuring tools, we provide highly detailed anatomic descriptions of the CNs and measurements of the diameter of selected segments. Specifics of the developmental stages of E14.5 mice and anatomic norm variations were acknowledged. Using the provided data as reference enabled us to objectively diagnose CN abnormalities, such as abnormal formation of CN3 (Col4a2), neuroma of the motor portion of CN5 (Arid1b), thinning of CN7 (Rpgrip1l) and abnormal topology of CN12 (Cc2d2a). Although, in a first glimpse perceived as unspectacular, defects of the motor CN5 or CN7, like enlargement or thinning can cause death of newborns, by hindering feeding. Furthermore, abnormal topology of CN12 was recently identified as a highly reliable marker for low penetrating, but potentially lethal defects of the central nervous system.